Lipidomics Reveals Seasonal Shifts in a Large-Bodied Hibernator, the Brown Bear - Giroud, Sylvain; Chery, Isabelle; Bertile, Fabrice; Bertrand-Michel, Justine; Tascher, Georg; Gauquelin-Koch, Guillemette; Arnemo, Jon M.; Swenson, Jon E.; Singh, Navinder J.; Lefai, Etienne; Evans, Alina L.; Simon, Chantal; et al. (Frontiers in Physiology, 2019)
Prior to winter, heterotherms retain polyunsaturated fatty acids (‘PUFA’), resulting in enhanced energy savings during hibernation, through deeper and longer torpor bouts. Hibernating bears exhibit a less dramatic reduction (2-5°C) in body temperature, but lower their metabolism to a degree close to that of small hibernators. We determined the lipid composition, via lipidomics, in skeletal muscle and white adipose tissues (‘WAT’), to assess lipid retention, and in blood plasma, to reflect lipid trafficking, of winter hibernating and summer active wild Scandinavian brown bears (Ursus arctos). We found that the proportion of monounsaturated fatty acids in muscle of bears was significantly higher during winter. During hibernation, omega-3 PUFAs were retained in WAT and short-length fatty acids were released into the plasma. The analysis of individual lipid moieties indicated significant changes of specific fatty acids, which are in line with the observed seasonal shift in the major lipid categories and can be involved in specific regulations of metabolisms. These results strongly suggest that the shift in lipid composition is well conserved among hibernators, independent of body mass and of the animals’ body temperature.